Regions from the ground up: a network partitioning approach to regional delineation. (June 2020) - Hamilton, Ruth; Rae, Alasdair
In this paper, we consider the question of what is 'in' a region, from an economic perspective, based on commuting data. This follows a long line of studies on labour market delineation, including the widely used 'travel-to-work area' approach. Using Combo, a network partitioning algorithm, we analyse commuting data from the 2011 UK Census in order to define a discrete set of regions. Our aim is twofold: to contribute to methodological advances in regional delineation, and to produce results that have real-world utility. Following the introduction, we review previous work, before describing our data and methods. Our approach produces 17 new 'regions' for Scotland, in contrast to the existing set of 32. Our view is that algorithmic approaches to regional delineation have much to offer in a policy setting, but this must be tempered by the fact that regions, however defined, are inherently political constructs.